2021
DOI: 10.1002/mrm.28770
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐brain amide CEST imaging at 3T with a steady‐state radial MRI acquisition

Abstract: Purpose: To develop a steady-state saturation with radial readout chemical exchange saturation transfer (starCEST) for acquiring CEST images at 3 Tesla (T). The polynomial Lorentzian line-shape fitting approach was further developed for extracting amideCEST intensities at this field. Method: StarCEST MRI using periodically rotated overlapping parallel lines with enhanced reconstruction-based spatial sampling was implemented to acquire Zspectra that are robust to brain motion. Multi-linear singular value decomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 33 publications
(104 citation statements)
references
References 73 publications
2
80
0
Order By: Relevance
“…Lower saturation power and longer saturation length will lead to a larger contribution from Guan proton to CEST signal at 2 ppm. On contrary to CrCEST in brain, GuanCEST contrast shows an opposite trend regarding pH reduction, which means lower pH yields higher GuanCEST contrast as evidenced by both eggwhite phantom ( Sui et al, 2021 ) and ischemic stroke studies ( Jin et al, 2017 ; Zhou et al, 2019 ). Therefore, in practice, appropriate saturation parameters should be chosen to ensure the CEST signal at 2 ppm is dominated by Cr.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Lower saturation power and longer saturation length will lead to a larger contribution from Guan proton to CEST signal at 2 ppm. On contrary to CrCEST in brain, GuanCEST contrast shows an opposite trend regarding pH reduction, which means lower pH yields higher GuanCEST contrast as evidenced by both eggwhite phantom ( Sui et al, 2021 ) and ischemic stroke studies ( Jin et al, 2017 ; Zhou et al, 2019 ). Therefore, in practice, appropriate saturation parameters should be chosen to ensure the CEST signal at 2 ppm is dominated by Cr.…”
Section: Discussionmentioning
confidence: 88%
“…For CrCEST study, the peak is much close to the water signal. In order to improve the fitting, an updated background function was introduced by including one Lorentzian function to account for the water direct saturation (DS) ( Sui et al, 2021 ): where the polynomial function ( C 2 + C 3 · Δω) was implemented to fit the background, consisting of magnetization transfer contrast (MTC) and exchanging protons such as amines and hydroxyls. We found that a linear function was sufficient to fit this combined background line shape between 1–3.5 ppm.…”
Section: Methodsmentioning
confidence: 99%
“…A reliable extraction of the amide and guanidyl signals from the background of other magnetization transfer signals (i.e. pH-independent) was realized by a separate firstorder polynomial and Lorentzian-fit 14,24,61 (Equation 10). In order to assess the specificity of the pH-dependent signals extracted by the fit model, the resulting MTR Rex (pH) curves were investigated, which served as a kind of ground truth.…”
Section: Discussionmentioning
confidence: 99%
“…Since the quantification of Z-spectra is exquisitely sensitive to static magnetic field (B 0 ) inhomogeneity, which exists in most MRI scanners, B 0 correction is needed. Typically B 0 correction is performed in two steps: (i) Generate a B 0 map: the B 0 map can be obtained by estimating the minimum of interpolated/fitted Z-spectra [48,171,172], water saturation shift referencing (WASSR) [173], or other B 0 mapping methods [174][175][176].…”
Section: Cest Postmentioning
confidence: 99%
“…After B 0 correction, it is sometimes suggested performing B 1 correction if the scanner has large B 1 inhomogeneity [35,176]. Similar to B 0 correction, B 1 correction includes two steps: (i) Generate B 1 map: the B 1 map can be acquired using flip-angle mapping [35,177], double angle method (DAM) [174,178], or other B 1 mapping methods [175,176]. (ii) Correct B 0 inhomogeneity for Z-spectra or CEST contrasts: the relative values on B 1 map are applied to correct the corresponding Z-spectra or CEST contrasts on a pixel-by-pixel basis.…”
Section: Cest Postmentioning
confidence: 99%